2020
DOI: 10.2147/opth.s256423
|View full text |Cite
|
Sign up to set email alerts
|

<p>Twelve-Month Outcomes of Stand-Alone Excisional Goniotomy in Mild to Severe Glaucoma</p>

Abstract: Purpose To describe 12-month intraocular pressure (IOP) and medication use outcomes following excisional goniotomy (EG) as a stand-alone procedure in eyes with medically uncontrolled glaucoma. Methods This was a retrospective analysis of data from surgeons at 8 centers (6 US, 2 Mexico). Eyes with glaucoma undergoing standalone EG with a specialized instrument (Kahook Dual Blade, New World Medical, Rancho Cucamonga, CA) for IOP reduction and followed for 12 months postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 38 publications
2
27
1
Order By: Relevance
“…Regeneration and scaring of the angle tissue in both techniques may progress over years, and lead to higher IOP at 18 and 24 months than those at three months in both the phaco-KDB and external phaco-trabeculotomy cohorts. In previous reports, re-elevation of IOP 18 or increase in number of postsurgical medications after the canal surgery 17 had been suggested without scientific analysis for the reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regeneration and scaring of the angle tissue in both techniques may progress over years, and lead to higher IOP at 18 and 24 months than those at three months in both the phaco-KDB and external phaco-trabeculotomy cohorts. In previous reports, re-elevation of IOP 18 or increase in number of postsurgical medications after the canal surgery 17 had been suggested without scientific analysis for the reasons.…”
Section: Discussionmentioning
confidence: 99%
“…As a first step of external phaco-trabeculotomy, cataract surgery was performed as a first step, and trabeculotomy procedures followed techniques described previously. 17 A metal trabeculotomy probe (Inami Co., Tokyo, Japan) was inserted into the Schlemm’s canal and in-rotated to disrupt the inner wall of the Schlemm’s canal at superior 120 circumferential degrees. Thereafter the scleral flap was secured to be watertight by five 10–0 nylons.…”
Section: Methodsmentioning
confidence: 99%
“…The success of IOP reduction seems to depend on the type of glaucoma being treated, with 40%-100% of the eyes achieving a ≥20% reduction in IOP. 26,27 Eyes with OAG and its subtypes appear to reach the 20% reduction mark 42%-72% of the time, whereas ACG patients appear to reach that 20% reduction mark up to 100% of the time. [26][27][28] When the uveitic glaucoma patients with elevated IOP were studied, only about 38% of them achieved the 20% reduction mark.…”
Section: Kahook Dual Blade ®mentioning
confidence: 95%
“…26,27 Eyes with OAG and its subtypes appear to reach the 20% reduction mark 42%-72% of the time, whereas ACG patients appear to reach that 20% reduction mark up to 100% of the time. [26][27][28] When the uveitic glaucoma patients with elevated IOP were studied, only about 38% of them achieved the 20% reduction mark. 29 Although the retrospective studies referenced above focus on KDB as a standalone procedure, KDB has been shown to be similarly effective with cataract surgery.…”
Section: Kahook Dual Blade ®mentioning
confidence: 95%
“…MIGS denotes a group of minimally invasive ab-interno procedures that have shown promise in the reduction in IOP and medication burden in patients with glaucoma while also significantly decreasing the risk of complications, such as hypotony. [5][6][7] Goniotomy performed with the Kahook Dual Blade ([KDB] New World Medical, Rancho Cucamonga, CA) is a type of Schlemm's canal MIGS procedure that has shown success in lowering IOP and reducing the medication burden in adult glaucoma patients as both a stand-alone procedure (KDB) 8,9 and combined with phacoemulsification (phaco-KDB). 5,7,10 The design of the parallel blade with a ramp allows a precise excision of the diseased trabecular meshwork en bloc to allow the aqueous humor to directly drain through the Schlemm's canal into the collector channels.…”
mentioning
confidence: 99%